Underreporting of occupational cancers in Denmark - Danø, H.; Skov, T.; Lynge, Elsebeth (Scandinavian Journal of Work, Environment & Health, 1996)
' ' OBJECTIVES ': 'The goal of the study was to investigate whether the reporting of occupational cancers has improved in Denmark since 1987 and whether medical records currently have better information on occupational exposures.' ' METHODS ': 'All cases of pleural mesothelioma and sinonasal adenocarcinoma and 766 randomly selected adenocarcinomas of the lung diagnosed between 1983 and 1990 were identified from the Cancer Register. These cases were traced in the Register of Reported Occupational Diseases and in the records of the National Board of Industrial Injuries. Medical records for patients not reported to the Register of Reported Occupational Diseases were requested from hospitals and the data on work-related exposure were retrieved.' ' RESULTS ': 'For pleural mesotheliomas the frequency of reporting increased from 43% in 1983–1987 to 53% in 1988–1990. The frequency of reporting of sinonasal adenocarcinomas decreased from 34 to 20% in these periods. Of the adenocarcinomas of the lung, 1% had been reported.' ' CONCLUSION ': 'Overall the reporting of occupational cancer has not improved in Denmark since 1987.
Keywords: exposure; information; occupational cancer reporting